HUBUNGAN KETIDAKPUASAN TUBUH DENGAN KECENDERUNGAN GANGGUAN MAKAN PADA REMAJA PUTRI PENGGUNA INSTAGRAM - Anindita Widhayaka Ma'rifah; Ahmad Chuisairi (Ridwan Institute, 2022)
This study aims to determine the relationship between body dissatisfaction and eating disorder tendencies in adolescent girls who uses Instagram. Body dissatisfaction is the negative perception of the body, comparing body with others, preoccupation with body, and changes in body dissatisfaction. Eating disorder tendencies is a disturbed eating pattern including behaviors of dieting, bulimia, and food preoccupation, as well as oral control. This research was conducted using a cross-sectional survey method. A total of 34 participants (M=17.2, SD=1.58) answered the Eating Attitudes Test (EAT-26) and Body Shape Questionnaire (BSQ-34). Data was analyzed empirically with Pearson correlation test. The results of the study revealed that there was a significant but weak relationship between body dissatisfaction and eating disorders tendencies in adolescent girls who uses Instagram (r=0.385 p=0.025). In addition, participant’s demographic data of body mass index is correlated with whether the individual is on a diet, the presence of dieting behaviors, and oral control. Penelitian ini bertujuan untuk menemukan hubungan ketidakpuasan tubuh dengan kecenderungan gangguan makan pada remaja putri pengguna Instagram. Ketidakpuasan tubuh yang dimaksud adalah persepsi negatif akan tubuh, membandingkan tubuh dengan orang lain, body preoccupation, dan perubahan akan ketidakpuasan tubuh. Kecenderungan gangguan makan yang dimaksud merupakan pola makan yang terganggu meliputi dieting, bulimia dan food preoccupation, serta kontrol oral. Penelitian ini dilakukan dengan metode cross-sectional survei secara daring. Sebanyak 34 partisipan (M=17.2, SD=1.58) menjawab Eating Attitudes Test (EAT-26) dan Body Shape Questionnaire (BSQ-34). Data dianalisis secara empiris dengan uji korelasi Pearson. Hasil penelitian ini mengungkapkan adanya hubungan signifikan namun lemah antara ketidakpuasan tubuh dengan kecenderungan gangguan makan pada remaja putri pengguna Instagram (r=0.385 p=0.025). Selain itu, data demografis Indeks Massa Tubuh partisipan berkorelasi dengan apakah individu sedang dalam keadaan diet, munculnya perilaku-perilaku dieting dan kontrol oral.